2003
DOI: 10.1016/s0920-5861(03)00382-1
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and structural properties of SnxTi1−xO2 solid solutions: a periodic DFT study

Abstract: The structural and electronic properties of selected compositions of Sn x Ti 1−x O 2 solid solutions (x = 0, 1/24, 1/16, 1/12, 1/8, 1/6, 1/4, 1/2, 3/4, 5/6, 7/8, 11/12, 15/16, 23/24 and 1) were investigated by means of periodic density functional theory (DFT) calculations at B3LYP level. The calculations show that the corresponding lattice parameters vary non-linearly with composition, supporting positive deviations from Vegard's law in the Sn x Ti 1−x O 2 system. Our results also account for the fact that che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 47 publications
9
50
0
2
Order By: Relevance
“…[41][42][43][44][45] In fact, DFT has been applied to evaluate the stability of stoichiometric pure SnO 2 and TiO 2 surfaces showing that for both crystals the (110) surface is the most favored. Moreover, the Sn 1-x Ti x O 2 bulk system has been studied by DFT 46 confirming the experimentally measured variation from Vegard's law for the rutile lattice parameters. …”
Section: Introductionsupporting
confidence: 72%
“…[41][42][43][44][45] In fact, DFT has been applied to evaluate the stability of stoichiometric pure SnO 2 and TiO 2 surfaces showing that for both crystals the (110) surface is the most favored. Moreover, the Sn 1-x Ti x O 2 bulk system has been studied by DFT 46 confirming the experimentally measured variation from Vegard's law for the rutile lattice parameters. …”
Section: Introductionsupporting
confidence: 72%
“…In addition, the shift of the band position may promote the separation of photoexcited electrons and holes, which is also favorable for photocatalytic reactions. 42,43 The formation of more structural defects may be another possible factor contributing to the enhanced photoactivity. As Yu et al 17 suggested, the structural defects may ionsorb oxygen as photoactive O -species and lead to increased photocatalytic activity.…”
Section: Photocatalytic Activitymentioning
confidence: 99%
“…22 These two effects can be the key factors controlling the rate for the photo-generated electron/hole recombination. These theoretical results 23 are capable of explaining the enhancement of photo-activity in Sn x Ti 1-x O 2 solid solutions.…”
Section: Introductionmentioning
confidence: 73%